The role of municipalities in transformation towards more sustainable construction : the case of wood construction in Finland - Salmi, Asta; Jussila, Jaakko; Hämäläinen, Mervi (Routledge, 2022)
Transformation towards more sustainable construction calls for actions from representatives of different sectors and societal levels. Previous studies have investigated companies and national policies as promoters of change, but neglected municipalities as relevant actors. Municipalities influence construction as they are trailblazers when realizing their own building projects, as well as regulators, whose planning decisions affect local and urban development. We investigate the role of municipalities in driving sustainability transformation in construction, in particular, in relation to wood construction. The empirical study relies on data collected in Finland through a comprehensive survey among municipalities and qualitative interviews. Key factors in municipal considerations are energy efficiency and carbon neutrality goals. Regulations and norms related to construction influence municipal activities as well. We find various drivers (e.g. supportive planning) and barriers (e.g. cost concerns) to wood construction. National programmes promoting wood construction have induced gradual changes and led to some municipal pilot projects. Despite these positive examples, it seems to take time before municipalities adopt wood construction more extensively. Simultaneously, their position at the intersection of different actors and activities involved in construction provides a fruitful base for promoting sustainable construction.
Keywords: business administration; municipality; public sector; sustainability; wood; fi=Markkinointi|en=Marketing|